(untitled) (The Review of Diabetic Studies, 2024)
Background: Modern dentistry has witnessed remarkable advancements in biomaterials designed to improve both aesthetic outcomes and functional performance in restorative treatments. Materials such as ceramics, resin composites, zirconia, bioactive glass, and hybrid materials have significantly transformed clinical practice by offering enhanced durability, biocompatibility, and aesthetic integration with natural dentition. Objective: This systematic review aims to evaluate the clinical performance of modern dental biomaterials in achieving aesthetic and functional restoration outcomes. Methods: A systematic search was conducted across major databases including PubMed, Scopus, Web of Science, and Embase to identify relevant clinical and laboratory studies published in recent years. Studies evaluating restorative biomaterials in terms of aesthetics, durability, mechanical strength, longevity, and patient satisfaction were included. The study selection process followed PRISMA guidelines. Results: The included studies demonstrated that modern biomaterials, particularly zirconia-based ceramics, nanocomposite resins, and bioactive materials, provide improved mechanical strength, enhanced esthetics, and long-term clinical stability. Conclusion: Advanced dental biomaterials significantly enhance restorative outcomes by combining aesthetic excellence with functional durability, supporting their widespread adoption in contemporary restorative dentistry.